Nursing clinical supervision, clinical audit and evidence implementation project - Vargas-Bermúdez, Zeidy; Cubero-Alpízar, Consuelo (Horizonte Sanitario, 2023)
Objective: To implement the best scientific evidence in the clinical supervision of ICUs by applying the JBI clinical audit tool for the optimization of the practice of clinical supervision in intensive care units. Materials and methods: This project used the JBI evidence implementation framework, based on the audit and feedback process together with a structured approach to identify and manage barriers to compliance with recommended clinical practices. Results: Most supervisors have little time to supervise critical care areas. The baseline audit showed that, of the 8 criteria set by JBI to assess clinical supervision, only three achieved 80% compliance by supervisors. Conclusions: The JBI clinical audit model allowed the identification of a series of criteria that were affecting clinical supervision and the establishment of a work plan template to strengthen and standardize the work of nursing supervision. Keywords: Nursing Supervision, Clinical Audit, Nursing, Evidence-Based Clinical Practice.